Time series analysis forecasting and control - Box George E P; Jenkins Gwilym M; Reinsel Gregory C (New Jersey John Wiley, 2008)
This book is concerned with the building of stochastic(statistical) models for time series and their use in important areas of application. It includes the topics of forecasting, model specification, estimation, & checking, transfer function modeling of
Keywords: Feedback control systems-mathematical models; Prediction theory; Time-series analysis; Transfer functions